Pre‐genetics clinic resource evaluation for adults with intellectual disability: The pre‐genetics clinic aid. Issue 4 (4th April 2020) - Kotwal, Huafrin; Fleming, Jane; Barlow‐Stewart, Kristine; Boyle, Jackie; Silberbauer, Letitia; Leffler, Melanie; Murray, Lucinda; Palmer, Elizabeth E.
Abstract: People with intellectual disability (PWID) consistently identify the importance of health service information that is accessible and relevant. Resources tailored to the information and support needs of PWID can facilitate inclusivity in their health care (including access to genomic medicine) and improve healthcare outcomes. Despite the fact that PWID are commonly referred to genetics services, there is a lack of appropriate resources to help them prepare for their appointments. We therefore aimed to evaluate the feasibility and acceptability of a booklet for PWID to read with their carers prior to their genetics appointment, to help them prepare for what they may experience. With input from Easy to Read experts and PWID who were members of the New South Wales (NSW) Council for Intellectual Disability, the information booklet 'Getting ready for your visit to the genetics clinic' was produced. Australian healthcare professionals (HCP) familiar with clinical genetics services were invited to complete an anonymous online survey designed to assess perceived relevance, readability, and utility of the resource. Recruitment of HCPs was pursued via affiliated clinical services and email distribution through clinical genetics organizations. Sixty‐six HCPs completed and submitted the survey. The results demonstrated that HCPs believed the booklet represented a typical clinical genetics service appointment and that the majority would provide a copy of the resource to clients and their carers. They reported that the booklet was easy to understand and entailed appropriate content and images which were presented clearly and simply. Some minor modifications were recommended and incorporated into the resource. A model of customizable booklets such as this could be transferrable across clinical genetics services and guide development of other resources for PWID. This may help to reduce healthcare disparities, improve client satisfaction, and facilitate involvement of PWID in their own healthcare decisions.